Analisis Pengembangan Media Pembelajaran Berbasis Game Interaktif Edunomic Adventure Pada Pembelajaran Ekonomi - Rahman, Rahman; Eriawaty, Eriawaty; H, Fendy Hariatama; Kharisma Nugraha Putra; Grace Evelina Buji; Alexandro, Rinto (Edunomics Journal, 2024)
The problem that is often found in learning economics is that teachers still use little learning media, especially technology-based learning media. The purpose of this research is to produce learning media based on edunomic adventure interactive games that are categorized as feasible, easy and effective for use in economic learning activities. This study uses development research or Research and Development (R&D) with the ADDIE model, namely Analysis, Design, Development, Implementation and Evaluation. The instrument used by researchers in this study is an expert validation sheet which will be validated by material experts and media experts to determine the level of quality and feasibility of edunomic adventure interactive game-based learning media that will be tested. Furthermore, giving questionnaires to students to determine the effectiveness of using learning media based on edunomic adventure interactive games. Based on the results of validation conducted by media experts on learning media based on interactive games edunomic adventure with a score of 86% in the category very valid to be used as a learning medium in economic lessons. Furthermore, the assessment of material experts on the material presented in the edunomic adventure interactive game-based learning media scored 85% in the category very valid for use as an economic learning media. The results of the assessment conducted by students on learning media based on interactive games edunomic adventure with a score of 88%, included in the category very feasible to use in economic learning